A New Testament Biblical Theology : the unfolding of the Old Testament in the New - Beale, G. K. (Gregory K.), 1949- (Grand Rapids, Mich. : Baker Academic, 2011)
G. K. Beale examines how the New Testament storyline relates to and develops the Old Testament storyline. Beale argues that every major concept of the New Testament is a development of a concept from the Old and is to be understood as a facet of the inauguration of the latter-day new creation and kingdom. --from publisher description
Pt. 1. The biblical-theological storyline of Scripture -- pt. 2. The story of the inauguratend-time tribulation -- pt. 3. The story of the inaugurated end-time resurrection and new-creational kingdom as a framework for New Testament theology -- pt. 4. The story of idolatry and restoration as God's image in the inaugurated new creation -- pt. 5. The story of salvation as inaugurated end-time new creation -- pt. 6. The story of the work of the Spirit in the inaugurated end-time new creation -- pt. 7. The story of the Church as end-time Israel in the inaugurated new creation -- pt. 8. The distinguishing marks of the church as storyline facets of the end-time inaugurated new creation -- pt. 9. The story of Christian living as inaugurated end-time new-creational life -- pt. 10. Conculsion.
Includes bibliographical references (p. 963-987) and indexes.
Keywords: Bible. -- Theology; Bible. -- New Testament -- Relation to the Old Testament